PARAMETRIC ANALYSIS OF A MINIATURIZED INVERTED II SHAPED ANTENNA FOR WIRELESS SENSOR NETWORK APPLICATIONS - M. Shanmugapriya; M.A. Maluk Mohamed; J. William (ICTACT Journal on Communication Technology, 2015)
A compact and simple design of a CPW-fed planar antenna for wireless sensor network antenna application with a better size reduction is presented. The proposed antenna consists of an inverted ? shaped metal patch on a printed circuit board fed by a 50-O coplanar waveguide (CPW). The parametric analysis of length and width are made. The designed antenna’s physical dimensions are 32 mm (length) x 26 mm (width) x 1.6 mm (height). The antenna structure has been modeled and fabricated and its performance has been evaluated using a method of moment based electromagnetic simulator, IE3D .The return loss of -22.5 dB and VSWR of 1.34 dB are noted. The radiation pattern of the antenna proves that it radiates in all direction. The antenna is fabricated and tested and the measured results go in good agreement with simulated one.